Psychological, social, and motivational factors in persons who use drugs - Sana Shahrabadi; Amir Jalali; Rostam Jalali; Ali Gholami (BMC, 2020)
Abstract Background Persons who use drug need family and society's support in the process of treatment and rehabilitation. Therefore, it is imperative to determine the psychological, social, and motivational factors that can help them in the treatment process. The present study was an attempt to determine the relationship between psychological, social, and motivational factors and the demographics of persons who use drugs (PWUD). Methods An analytical cross-sectional study was carried out. TCU psychological functioning and motivation scales for the PWUD was first translated into Farsi and validated after securing permission from the copyright holder of the tool. Participants were 250 PWUDs under methadone therapy who were selected through convenient sampling. Before analyzing the collected data, validity and reliability of the tool were confirmed using confirmatory and exploratory factor analyses. Given the scale of demographical data, descriptive and analytic statistics were used to analyze the relationship between demographical variables and psychological, social, and motivational factors. Results The results of exploratory and confirmatory factor analyses showed that out of 83 statements in the original questionnaire, 55 statements categorized into 11 aspects were usable for Iranian population. The results showed that gender, income, and marital status affect psychological functioning of the PWUD (P < 0.05). However, education level, place of residence, and type of drug and consumption did not have a significant relationship with social functioning of the participants (p > 0.05). There was a significant relationship between age, number of children, and history of using drug and psychological functioning of the participants (P < 0.01). The results showed that the demographics did not have a notable effect on the participants' motivation for treatment; only marital status had a significant relationship with the participants' treatment readiness (P < 0.05). Conclusion As the results showed, the demographical variables could affect physical, psychological, and social functioning in the participants.